Analisis kinerja keuangan dan non keuangan pemerintah daerah kabupaten kampar - Zikri, Zarman; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is a case study in Kampar regency government. The purpose of this study is to analyze the financial performance of financial ratios based on the budget and analyze non-financial performance Kampar district local government public satisfaction index based on the public service to users of the service.In this study, the writer used descriptive analysis on Budget Realization Report by using financial ratios such as the ratio of Independence, Effectiveness and Efficiency Ratio, Activity Ratio, Debt Service Coverage Ratio, and Ratio Growth and uses Community Satisfaction Index which calculated using the weighted average value of each indicator based services Kepmen.PAN 25, 2004.Based on the results of data analysis, it can be concluded that the financial performance of Kampar regency administration has shown the average financial performance of the stable. Where the results of the calculation of the percentage ratio of each year experiencing a positive trend. While the Community Satisfaction on Service Delivery in Kampar regency government is good. Where the results of Customer Satisfaction Index of 14 indicators of service seen in 25 Kepmen.PAN 2004 after the converted value is 71.8875 and quality of service B.Keywords : Performance, Independence Ratio, Effectiveness and Efficiency Ratio, Activity Ratio, Debt Service Coverage Ratio, Ratio Growth, and Community Satisfaction.